Former President Fidel Ramos visits DLSU-Manila - De La Salle University, Manila (Animo Repository, 2000)
Former President Fidel Ramos visits DLSU-Manila on February 3 to formally turn-over his book donation to the University. He also visits the on-going exhibit Philippines 2000 and Beyond. The exhibit, which features photos and memorabilia pertaining to the 1986 EDSA Revolution, is sponsored by the Yuchengco Center for East Asia and the University Library.